Measuring personal growth and development in context: Evidence of validity in educational and work settings - Anderson, B.; Meyer, John; Vaters, C.; Espinoza, J. (Springer Nature, 2019)
Consistent with the trend toward viewing psychological well-being as more than the absence of illness, we developed an instrument—the personal growth and development scale (PGDS)—that can be used to assess positive change in well-being attributable to context-specific experiences. As part of the validation process, we examined relations between the PGDS and measures of need satisfaction and autonomous motivation in students (N = 241) and employees (N = 468). In the student sample, we also examined relations with engagement and burnout. The findings supported our hypothesis that need satisfaction, autonomous motivation and engagement would relate positively with the PGDS, and that burnout would relate negatively. In a second student sample (N = 377), we collected longitudinal data to investigate how global psychological well-being relates to personal growth and development over the course of an academic term. We found that initial levels of global well-being predicted positive changes in growth and development and replicated earlier findings regarding relations between the PGDS, need satisfaction and autonomous motivation. Future applications of the PGDS for research and practice are discussed.